Pancasila: Filosofi Pembentukan Peraturan Perundang-Undangan di Indonesia - Auliya Putri Dewi; Rida Kasih Karunita; Yonathan Azriel Taneli (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Pancasila as the Indonesian state philosophy plays a central role in the formation of laws and regulations in this country. This article explains how the basic values ​​of Pancasila are the main basis for the legislative and law formation process in Indonesia. In this context, Pancasila not only functions as a source of moral and ethical values ​​in drafting laws, but also as a guideline for maintaining social justice, democracy, unity and national security. This study examines various aspects and practical implementation of the role of Pancasila in the Indonesian legal context, including its influence on public policy and the legislative process.